Indonesian Shariah Bank Regulation : Practices, Practitioners and Praxis - Muhammad Adam HR (Faculty of Law, Universitas Sebelas Maret, 2021)
The potential merger of three state-owned Sharia banks into PT. Bank Syariah Indonesia Tbk is the subject of this research, which looks at the benefits and drawbacks. This study employs a qualitative descriptive method in which data is collected and analyzed inductively. According to the findings, PT. Bank Syariah Indonesia Tbk finds solutions to Indonesia's economic difficulties. On the other side, PT. Bank Syariah Indonesia Tbk is potentially susceptible due to a lack of policy support from relevant stakeholders; in other words, the merging of Sharia Banks does not bode well for Indonesia's economy. The goal of this research is to look at the potential and challenges that PT. Bank Syariah Indonesia Tbk is facing, as well as the prospect of PT. Bank Syariah Indonesia Tbk providing a solution to economic problems. After the merger, PT. Bank Syariah Indonesia Tbk requires government encouragement in the form of associated policies in the form of rules and regulations governing the company's operation. The findings of this study show that PT. Bank Syariah Indonesia Tbk is more hopeful about offering sharia-compliant services to the community. After the merging of three state-owned Sharia banks into PT. Bank Syariah Indonesia Tbk, this study evaluates the prospects and obstacles for establishing Sharia banks.